Predictors of bullying victimization among early adolescents in junior high schools: A cross-sectional study - Juli, Romida; Sarfika, Rika; Basmanelly; Saifudin, I Made Moh. Yanuar; Abdullah, Khatijah Lim (Belitung Nursing Journal, 2025)
Background: Bullying victimization among adolescents is a significant public health issue in Indonesia, with limited research on factors such as self-esteem and peer pressure within local cultural contexts. Objective: This study aimed to identify the factors influencing bullying victimization among early adolescents in junior high schools. Methods: A cross-sectional study was conducted with 401 junior high school students from March to May 2024. Participants were selected through stratified random sampling, and data were collected using validated instruments, including the Revised Olweus Bully/Victim Questionnaire, Rosenberg Self-Esteem Scale, Peer Pressure Inventory, Depression Anxiety Stress Scales for Youth, and Parent Authority Questionnaire. Descriptive statistics, chi-square tests, and ordinal logistic regression were employed for analysis. Results: Among participants, 23.2% reported being victims of bullying. Multivariate analysis identified high peer pressure as the strongest predictor of bullying victimization (OR = 5.64, 95% CI = 2.12–15.03, p <0.001), while authoritarian parenting style emerged as potentially protective (OR = 0.34, 95% CI = 0.13–0.87, p = 0.024) compared to authoritative parenting. Self-esteem, depression, and social media use did not demonstrate significant independent associations with victimization in the final model, despite showing significant bivariate relationships. Conclusion: Peer pressure emerged as the critical predictor of bullying victimization among early adolescents, with authoritarian parenting demonstrating an unexpected protective effect within this cultural context. School-based interventions should prioritize peer-focused strategies while considering culturally specific parenting dynamics. These findings highlight the importance of developing prevention approaches that account for Indonesia's collectivist social framework.